Outcome of COVID-19 in interstitial lung disease patients treated with anti-inflammatory drugs and antiviral drugs. Issue 7 (July 2022) - Yamaya, Takafumi; Hagiwara, Eri; Baba, Tomohisa; Iwasawa, Tae; Ogura, Takashi
Abstract: A recent study reported that patients with interstitial lung disease (ILD) are at increased risk of death from coronavirus disease 2019 (COVID-19). However, there are no studies on the outcome of COVID-19 patients with preexisting ILD treated with corticosteroids or antiviral drugs. We extracted 26 patients with preexisting ILD by medical records and HRCT pattern. Of 503 patients with COVID-19, we selected 52 patients as control matched for age and sex. Twenty out of the 26 ILD patients (76.9%) received corticosteroid therapy, and 23 patients (88.5%) also received antiviral treatment with remdesivir or favipiravir. Although no statistical difference was found, the proportion of severe patients in ILD group tended to be higher than in non-ILD group (23.1% vs. 42.3%; p = 0.114). Also, mortality rate in ILD group tended to be higher than in non-ILD patients (11.5% vs. 3.8%; p = 0.326). In univariate analysis to evaluate risk factors for severe condition, diagnosis of idiopathic pulmonary fibrosis, usual interstitial pneumonia pattern, and honeycomb lung were not risk factors of severe disease. Treatment with corticosteroids, antiviral drugs, and immunosuppressive agents may affect the outcome of COVID-19 patients with ILD.